2008
DOI: 10.1007/s00520-008-0426-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of educational intervention on nurses’ knowledge, attitudes, and behavioral intentions toward supplying artificial nutrition and hydration to terminal cancer patients

Abstract: The educational intervention remarkably improved nurses' knowledge and attitudes regarding supplying terminal cancer patients with ANH. As for the changes in the behavioral intentions, it requires long-term moral and ethical training and communication. The results of this research emphasized the importance of educational interventions, which should be considered seriously in future reference nursing education program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Regarding the adequate sequence of suction (tracheostomy, nose, and mouth [8]) statistically significant improvement on knowledge was also observed: from 45.4% who informed the right answer in the pretest to 91.8% in the posttest (p<0.01). Other studies verified that educational intervention improved nurses knowledge regarding cancer patients care [5,6]. The results aspects described herein reinforce the relevance of continued education as an effective resource to stimulate the development of theoretical knowledge in an attempt to improve the performance of nursing personnel procedures related to tracheostomized patients.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Regarding the adequate sequence of suction (tracheostomy, nose, and mouth [8]) statistically significant improvement on knowledge was also observed: from 45.4% who informed the right answer in the pretest to 91.8% in the posttest (p<0.01). Other studies verified that educational intervention improved nurses knowledge regarding cancer patients care [5,6]. The results aspects described herein reinforce the relevance of continued education as an effective resource to stimulate the development of theoretical knowledge in an attempt to improve the performance of nursing personnel procedures related to tracheostomized patients.…”
Section: Resultssupporting
confidence: 79%
“…In a suctioning session how many suctioning procedures (introduction of the suctioning probe into the stoma) should ideally be performed? The questionnaire was elaborated based on observations from clinical practice as well as on information from the literature [4][5][6][7].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, nurses' scores on knowledge and attitudes increased after a 1-hour lecture; however, the lecture did not influence their behavioral intentions. 16 In Japan, the study showed that nurses' scores of knowledge and confidence increased significantly after a 5-hour workshop and that 80% of the nurses reported that they would perform 6 recommended practices to assess patients' and patients' families' worries, to provide mouth care, to assess patient pain, and to modify the infusion based on the patient's lifestyle. 17 These results indicate that nurses' ANH knowledge might influence their intentions to apply ANH in practice.…”
Section: Discussionmentioning
confidence: 98%
“…The questionnaire has good content validity and reliability. 15,16 The questionnaire comprised 6 parts, including demographic characteristics, knowledge of provision of ANH for patients with terminal cancer (15 items), attitudes about providing ANH for patients with terminal cancer (17 items), behavioral intentions about providing ANH for patients with terminal cancer (2 items), subjective norms that influence provision of ANH for patients with terminal cancer (4 items), and factors influencing provision of ANH for patients with terminal cancer (11 items). For the factors influencing provision of ANH for patients with terminal cancer, exploratory factor analysis was conducted.…”
Section: Measurementmentioning
confidence: 99%
“…Recent studies have shown how educational interventions are proving to be all the more promising in continuing education in nursing [27][28][29] . The interventions for nurses vary, can be based on different theories, and most often explore effectiveness of workshops, lectures, or educational programs on nurses' knowledge and attitudes.…”
Section: Introductionmentioning
confidence: 99%